1975
DOI: 10.1109/tmag.1975.1058684
|View full text |Cite
|
Sign up to set email alerts
|

Magnetization and design of multistrand superconducting conductors

Abstract: Magnetization of cabled and braided samples which are long compared to their transposition lengths has been measured in a uniform magnetizing field directed at right angles to their widths. A separated double pancake with nonuniform windings was constructed to produce a suitably uniform radial field in which long coiled samples could be placed. Magnetization losses have also been measured in the ISA I magnet at BNL. Results are compared with theories which are due to Wilson* and, basically, Morgan. 2 Also, des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1975
1975
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…We model the quench state-transition through a suitable transition-variable ξ ht . Joule losses are accounted as Q Ohm = J s · σ −1 ht J s , where the equivalent half-turn resistivity σ −1 ht is calculated using a reformulation of the Stekly approximation [17] for the current sharing regime [18], simplifying the extraction of the coil's equivalent resistance(Sec. II-D).…”
Section: Heat Balancementioning
confidence: 99%
“…We model the quench state-transition through a suitable transition-variable ξ ht . Joule losses are accounted as Q Ohm = J s · σ −1 ht J s , where the equivalent half-turn resistivity σ −1 ht is calculated using a reformulation of the Stekly approximation [17] for the current sharing regime [18], simplifying the extraction of the coil's equivalent resistance(Sec. II-D).…”
Section: Heat Balancementioning
confidence: 99%
“…According to [6] the concept of n-index was first introduced by Walters [7]. In an early work [8] Voelker observed that the logarithmic slope of the VAC slowly varies with field and current for a given sample of wire while it can be very different from sample to sample, due to broken filaments, twisting, metallurgical treatment, copper-to-superconductor bond or some other features.…”
Section: Empirical Modelsmentioning
confidence: 99%
“…* According to his tests, the braid was much more susceptible to induced magnetization currents than the Brookhaven scientists thought. 46 While this drew the concern of Hahn and one or two other insiders, the concern did not propagate.…”
Section: Phys Perspect 358mentioning
confidence: 99%